The protective effects of paeonol against epirubicin-induced hepatotoxicity in 4T1-tumor bearing mice via inhibition of the PI3K/Akt/NF-kB pathway. (25th January 2016) - Wu, Jing; Xue, Xia; Zhang, Bin; Jiang, Wen; Cao, Hongmei; Wang, Rongmei; Sun, Deqing; Guo, Ruichen
Abstract: Epirubicin is widely used for the treatment of various breast cancers; however, it has serious adverse side effects, such as hepatotoxicity, which require dose-adjustment or therapy substitution. Paeonol, an active component from Moutan Cortex, has a variety of biological activities, including preventing or reducing various toxicities induced by antineoplastics. Protection by paeonol against hepatotoxicity induced by epirubicin and the underlying mechanism of action were investigated in this study. Cytosolic enzymes in the serum and oxidative stress indices in the liver were determined. The protective effects were determined using the MTT assay in vitro or by evaluating the expression of apoptotic factors and crucial proteins in the PI3K/Akt/NF-kB pathway using western blot analysis. It is concluded that paeonol alleviates epirubicin-induced hepatotoxicity in 4T1-tumor bearing mice by inhibiting the PI3K/Akt/NF-kB pathway. Highlights: Epirubicin is widely used to treat breast cancer, but limited for its hepatotoxicity. Paeonol could alleviate epirubicin-induced hepatotoxicity in 4T1-tumor bearing mice. The mechanism relies on inhibiting the PI3K/Akt/NF-kB pathway.